Location choice, ownership structure and multinational performance. Issue 3 (1st October 2018) - Gu, Jinlong; Yang, Yong; Strange, Roger
Abstract : Purpose: This paper aims to link location choice and ownership structure to the debate on the multinationality–performance relationship. Design/methodology/approach: This paper draws on a panel data set that covers 1, 321 emerging economy multinational enterprises (EMNEs) and includes 4, 227 observations from 44 emerging economies between 2004 and, 2013. Findings: The empirical results find that multinationality has a positive effect on EMNEs' performance, and that this positive effect is larger for their investments in developed countries than in developing countries. The study also finds that this positive effect of foreign operation in developed countries switch to negative at higher levels of multinationality for privately owned EMNEs than for state-owned EMNEs. Originality/value: This paper provides new empirical evidence to support an institutional perspective of the internationalisation of EMNEs that are investing in developed countries, contributing to the multinationality-performance literature, highlighting the importance of foreign direct investment location decision and ownership structure.